Canadian Librarians as Research Ethics Board Members: An Exploratory Case Study - Lacroix, Denis (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2021)
Very little is known about Canadian librarians who sit on Research Ethics Boards (REBs) or Institutional Review Boards (IRBs). There is some background information on various roles of librarians on REBs, but that is usually from the perspective of one or two authors and often relating to the health sciences. Librarianship continues to evolve, especially in the areas of research data management, research support, and scholarly communication. It is, therefore, important to understand the changing expectations and responsibilities that librarians may have in Canada in order to encourage and support them as they meet institutional needs. This exploratory case study will document the reasons that motivate Canadian librarians to sit on REBs, the training they have received, the benefits achieved, and their overall experience.